2001
DOI: 10.14221/ajte.2001v26n1.5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Aboriginal Students to Schooling

Abstract: In this paper the attitudes of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Godfrey et al (2001) found that 42 per cent expressed this view and a similar proportion (39%) considered that their teachers didn't care about them. Drawn almost exclusively from the dominant Anglo-Australian community, teachers bring the attitudes and beliefs of the dominant community into the classroom.…”
Section: Problems With Schoolmentioning
confidence: 92%
See 2 more Smart Citations
“…Godfrey et al (2001) found that 42 per cent expressed this view and a similar proportion (39%) considered that their teachers didn't care about them. Drawn almost exclusively from the dominant Anglo-Australian community, teachers bring the attitudes and beliefs of the dominant community into the classroom.…”
Section: Problems With Schoolmentioning
confidence: 92%
“…For example, teachers may withdraw Indigenous students from classroom participation on the basis of their cultural identity or they may fail to listen to the explanations provided by such students when they are in trouble (Godfrey, Partington, Harslett & richer, 2001). Differential treatment is common and is complained about by Indigenous students.…”
Section: Problems With Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational aspirations There is clear consensus that Indigenous young people hold aspirations to complete secondary school (Craven et al 2005;Godfrey et al 2001;Harwood et al 2015). However, they are more likely than their nonIndigenous peers to want to depart school earlier (Craven and Marsh 2004;Craven et al 2005;De Bortoli and Cresswell 2004) and to plan to complete no further education past high school (De Bortoli and Cresswell 2004).…”
Section: Aspirationsmentioning
confidence: 99%
“…Studies conducted at the secondary school level revealed that Indigenous students are less likely to aspire to university in comparison to non-Indigenous students (Craven et al 2005;De Bortoli and Cresswell 2004). Importantly, it was also found that many Indigenous students do aim to go to university and attain a higher education (Craven and Marsh 2004;Craven et al 2005;Godfrey et al 2001;Harwood et al 2015;Nelson and Hay 2010;Walker et al 2008). Educational aspirations are also framed more generally by Indigenous students and their parents as the desire to receive 'a good education' (Lette et al 2009;Walker et al 2008).…”
Section: Aspirationsmentioning
confidence: 99%